Galois Theory and Modular Forms - Hashimoto, Ki-ichiro (Developments in Mathematics, 2004)
The key words for the book are "Galois groups", or more precisely "generic polynomials","Galois coverings of algebraic curves" and "Shimura varieties". The work includes surveys on branches of research areas and many articles, all critically refereed by experts, which present the latest research results with carefully written expository introductions. The topics cover a wide range which nonetheless have a common thread. This volume is suitable for advanced undergraduate and graduate students, as well as researchers